Studi Literatur Dampak Perkembangan Zaman Pada Perubahan Tata Rias Pengantin Jawa - Yusuf, Mardhiyya; Maghfiroh, Anik (Jurnal Tata Rias, 2024)
The rapid development of the times has influenced various aspects of life, including Javanese bridal make-up traditions. This article examines modifications to Javanese bridal make-up, especially for Muslim brides, to respond to modern aesthetic demands and the social changes that are occurring. This modification of make-up can be seen in changes in technique, use of cosmetics, and styling of the hijab which is more practical but still maintains traditional elements. Adjustments to bridal make-up in various regions, such as Sidoarjo, Trenggalek, Bojonegoro and Jogja, reflect efforts to maintain a balance between cultural values and the needs of today's brides. As a result, bridal make-up has become simpler and more minimalist, but still maintains deep cultural symbolism and philosophy. This article shows that modifications to Javanese bridal make-up are a solution to deal with the impact of changing times, so that traditions remain relevant and accepted by the younger generation.